Treatment for the Benign Childhood Epilepsy With Centrotemporal Spikes: A Monocentric Study - Kessi, Miriam; Yan, Fangling; Pan, Langui; Chen, Baiyu; Olatoutou, Eleonore; Li, Dong; He, Fang; Rugambwa, Tibera; Yang, Lifen; Peng, Jing; Yin, Fei (Frontiers in Neurology, 2021)
Background and purpose To date, there is no specific treatment guideline for the benign childhood epilepsy with centrotemporal spikes (BECTS). Several countries recommend levetiracetam, carbamazepine, sodium valproate, oxcarbazepine, and lamotrigine as first-line drugs. Nevertheless, some of these drugs are associated with cognitive decline. Available studies that investigated the efficacy of levetiracetam and sodium valproate on BECTS involved small sample sizes. This study aimed to evaluate the efficacy of levetiracetam and sodium valproate on cognition, and to investigate the prognostic factors for BECTS as whole. Methods Clinical data and treatment status of all patients with BECTS at Xiangya Hospital, Central South University followed from 2008 to 2013 were analysed retrospectively. Since electrical status epilepticus in sleep (ESES) has been confirmed to play a role in cognitive deterioration, in order to evaluate the response to drugs and their cognitive effects, we created two groups of patients according to the levels of spike wave index (SWI): group 1; 0-50% SWI and group 2; >50% SWI at the last follow up. Results A total of 195 cases were enrolled: 49.7% received monotherapies, 24.1% duotherapies and 27.2% polytherapies. Medications included; levetiracetam plus other drug (s) (75.9%), levetiracetam alone (32.8%), sodium valproate plus other drug (s) (31.3%), and sodium valproate alone (5.1%). After two years of treatment and follow up, 71% of the cases had a good seizure outcome, 15.9% had an improvement of SWI, and 91.7% had a normal DQ/IQ. Sodium valproate combined with levetiracetam, and sodium valproate alone correlated with good improvement of SWI, whereas, focal spikes were linked with poor improvement. For both groups (group 1 and group 2): monotherapy, levetiracetam alone, and a normal DQ/IQ at seizure onset correlated with good cognitive outcomes, in contrast, polytherapy, sodium valproate plus other drug (s), levetiracetam plus sodium valproate, an initial SWI of ≥85%, and multifocal spikes were linked to cognitive deterioration. Conclusions Monotherapy, particularly levetiracetam seems to be a good first-line therapy which can help in normalizing the electroencephalograph and preventing cognitive decline. Polytherapy, mostly the administration of sodium valproate seems to relate with poor cognition, therefore, it is recommended to avoid it.